The effect of acute consumption of HMB and creatine supplement on oxidative and antioxidant indices after resistance exercise in trained men - داریوش شیخ الاسلامی وطنی; کیوان احمدی (فیزیولوژی ورزش و فعالیت بدنی)
Introduction: The aim of this study was to determine the acute effect of HMB and Creatine supplementation on the oxidant and antioxidant indices on trained men after resistance exercise. Method: 10 active men with a mean age of 20±1.15 years, height: 172.2±4.82 cm, weight: 70.9±9.66 kg and body mass index: 24.04±2.44 kg/m2 was purposefully selected and then in a crossover clinical trial design was randomly divided into 4 groups. Resistance exercises including bench press, leg extensions, barbell curl, triceps extension, shoulder press and lat pull down were carried out at 80% 1RM. Prior to each resistance exercise session, subjects were randomized to Creatine, Creatine+HMB, HMB or placebo loading for 5 days. One-week washout was considered between supplementation periods. A day after the completion of each supplementation courses, blood samples were taken in the fasting state to evaluate the effect of supplementation on current research variables. Results: The results using ANOVA with repeated measurements showed that ingestion of creatine, HMB, or combined supplements has no effect on the serum levels of uric acid, bilirubin, malondialdehyde and glutathione peroxidase. Conclusion: Overall, the present research findings suggest that short term (5 days) creatine, HMB and combined Cr + HMB has no effect on the oxidant and antioxidant variations following acute resistance exercise.